2019
DOI: 10.1044/2019_jslhr-s-18-0340
|View full text |Cite
|
Sign up to set email alerts
|

In-Clinic and Standalone Internet Cognitive Behavior Therapy Treatment for Social Anxiety in Stuttering: A Randomized Trial of iGlebe

Abstract: Purpose iGlebe is an individualized, fully automated Internet cognitive behavior therapy (CBT) treatment program that requires no clinician contact. Phase I and II trials have demonstrated that it may be efficacious for treating the social anxiety commonly associated with stuttering. The present trial sought to establish whether the outcomes achieved by iGlebe are noninferior to those associated with in-clinic CBT from clinical psychologists. Method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 37 publications
2
24
0
Order By: Relevance
“…However, subclinical VRET may be particularly suited for delivery alongside speech therapy. Some authors have suggested that all PWS receiving speech therapy should also receive psychological treatment (23), given findings that mental health conditions can disrupt the progress made from speech therapy (72). Such is the highly entwined nature of comorbid stuttering and social anxiety, that cognitive and behavioral change are considered necessary for managing stuttering (73).…”
Section: Clinical Vs Subclinical Social Anxietymentioning
confidence: 99%
See 2 more Smart Citations
“…However, subclinical VRET may be particularly suited for delivery alongside speech therapy. Some authors have suggested that all PWS receiving speech therapy should also receive psychological treatment (23), given findings that mental health conditions can disrupt the progress made from speech therapy (72). Such is the highly entwined nature of comorbid stuttering and social anxiety, that cognitive and behavioral change are considered necessary for managing stuttering (73).…”
Section: Clinical Vs Subclinical Social Anxietymentioning
confidence: 99%
“…As such, treatments should consider the cognitive processes, thoughts, and behaviors associated with social anxiety in stuttering (11), as well as situational factors and practical considerations. Cognitive Behavioral Therapy (CBT) is considered the gold-standard treatment for anxiety disorders (15) and several studies have investigated its use for PWS (16)(17)(18), with some adopting protocols which consider stutteringspecific processes (14,(19)(20)(21)(22)(23)(24). This includes targeting speechrelated fears, and the safety behaviors and expectations that are common amongst PWS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is unclear what this discord reflects; however, it may reflect a conflict between stakeholders in the way we manage stuttering, or an evolution in our understanding of what stuttering treatment entails. An increasing efficacy evidence base for affective and cognitive-based interven-tions with adults who stutter is evident, including cognitive behavioural therapy and acceptance and commitment therapy (Beilby et al, 2012;Menzies et al, 2009Menzies et al, , 2019Sønsterud et al, 2020). Such approaches have demonstrated improvements in psychosocial functioning, speech fluency or both when treatments target both aspects of the disorder.…”
Section: Personal Factorsmentioning
confidence: 99%
“…VAL LIM: I definitely refer the patients to my colleagues beyond the discipline who are CBT trained. That said, I have directed patients to an online CBT programme (Menzies et al, 2019). SUE O'BRIAN: I do see a role for SLPs working through a comprehensive online CBT program with their clients.…”
Section: Persistent Stuttering: Should Slps Attempt Cognitive Behavior Therapy (Cbt) With Clients Who Stutter and Are Anxious?mentioning
confidence: 99%